A survey on the quality of standardized diabetes management in primary care facilities - YANG Rong; JIN Hua; SHI Ling; YI Chuntao; HOU Jin; CHEN Chen; HUAN Hongmei; NI Hengru; YU Dehua (Chinese General Practice Journal)
Background: The rising incidence of diabetes has led China to prioritize the management of type 2 diabetes within community health services. However, there remain gaps in standardized diabetes management in primary care facilities, particularly in terms of quality and capacity. Objective: This study aims to evaluate the current status of diabetes management and provide a systematic quality assessment. Recommendations for improvement are proposed based on identified issues. Methods: In May 2022, a survey was conducted involving 249 community health centers of Shanghai. A simple random sampling method was used to select 3,875 general practitioners(GPs), representing 50 % of the registered GPs at each center. Data were collected using a self-designed questionnaire. Results: All community health centers of Shanghai were able to conduct HbA1c tests; however, screening for diabetic complications was insufficient, with only 16.9 % offering nerve conduction velocity tests. The availability of oral hypoglycemic agents was relatively comprehensive, but insulin options were limited, with only 7.6 % of centers had novel GLP-1 available. Furthermore, only 57.4 % of centers had diabetes specialty clinics. GPs demonstrated strong adherence to diabetes management guidelines but had significant knowledge gaps in medication use, with correct responses regarding oral hypoglycemic agents at 27.9 % and insulin at 29.0 %. GPs tended to transfer new patients with high blood glucose or confirmed diabetic nephropathy to higher-level hospitals. Conclusion: The infrastructure, equipment, and medications for diabetes management in Shanghai's community health centers partially meet basic quality standards, but there are significant gaps in GPs' knowledge of diabetes medications. To improve diabetes management, efforts should focus on expanding complication screening, increasing the availability of novel hypoglycemic agents and insulin types, enhancing the development of diabetes specialty clinics, and providing GPs with further training to improve their diagnostic and treatment capabilities.